INTEGRASI BUDIDAYA JAMUR TIRAM DAN LELE GUNA MENINGKATKAN PENDAPATAN MASYARAKAT - Zasmeli Suhaemi; Sari Gando Hidayati; Zahanis Zahanis; Meita Lefi Kurnia; Zulmardi Zulmardi (Jurnal Hilirisasi IPTEKS, 2020)
Soft skill like how to manage useful land that be convenient for doing by people. These skills are expected to be a new source of income for people. For this goals, 30 student from four department Tamansiswa University implement the program was conducted for this activities. The location that choose for this implementation called Lubuk Minturun, that located in the district of Koto Tangah Kota Padang. People who live in Lubuk Minturun majority work as farmer. Approximately 60% of the people depend on the plantation and selling ornamental plants, they only obtained within a specified period or unpredictable incomes. Using land yard for businesses Mushrooms and catfish can be a revenue opportunity to increase people income. The method used in this activity were 4 steps: 1) socialization program, 2) training, 3) pilot project and 4) assistance, that involves 30 students. This program also involves three groups of people in RT 01, 02 and 03 of RW 010. Student which participation in this program also trained people for processing the mushroom and catfish as nuggets and meatballs. Based on the results of the activities can be concluded that the public response will be something new and beneficial life is very high. Mushroom production can increased revenue of Rp 22.800/pc mash room media and catfish production was Rp 352,000 every 500 fish. This is shown by the formation of three groups of people in RT 01, 02 and 03 of RW 010 still continued mushroom and catfish production.